PENGARUH GAYA KEPEMIMPINAN, KOMUNIKSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. INDOSTAR SUKSES MANDIRI MEDAN - Andre Fitriano; Bimbi Syahputra Lumbantobing; Agustina Agustina; Sehtembeate Munthe; Eko Prasasti Damanik (Universitas Methodist Indonesia, 2020)
The research aimed to examine the influence of leadership style, communication, and work discipline on employee performance at PT. Indostar Sukses Mandiri Medan. The population and sample in this study are all permanent employees. They were required to fill out a questionnaire. The analysis used in this study was multiple linear regression. The results showed that partially leadership style had a positive and significant effect on employee performance. Additionally, communication and work discipline had a positive and significant effect on the employee performance of PT Indostar Sukses Mandiri Medan. Simultaneously leadership style, communication and work discipline have a positive and significant effect on employee performance of PT. Indostar Sukses Mandiri Medan.